Component Resilience in Family Harmony in Omben Village - Imroatus Sa'adah (Universitas Muhammadiyah Palu, 2024)
The resilience of Islamic boarding school cooperatives in the economic order of society and students has been established for a long time. So that in Law 52 of 2009 concerning population development and establishing a definition of family resilience and prosperity as a family that has tenacity and toughness and contains material physical properties to live independently in achieving inner and outer happiness and economic resilience. This research method is qualitative. Meanwhile, this research was written using empirical legal research, which started as a primary based on field data from the community, through a process of observation and interviews. So this research is based on society and Islamic boarding schools, namely in the form of the Nahdlatut Thullab Islamic boarding school cooperative, in which there is a big contribution not only for students but for family resilience in the economy. Therefore, the results of research on component resilience in family harmony cannot be separated from the form Compontren's contribution to society and the factors and benefits and social aspects felt by the community and the students are found. So it is not surprising that the existence of components can help the economy of every community. Apart from that, there are also factors that with the existence of components, it can open up job vacancies for people so that they can also be helped economically and work together with their partners, so it is not surprising, if there are several aspects and several advantages that can be found in the community, it becomes more economical and be more grateful for what you have. So as to create family harmony and household resilience that is always happy physically and mentally.